A Hybrid 2D/3D Approach for Neural Differentiation Into Telencephalic Organoids and Efficient Modulation of FGF8 Signaling - Michele Bertacchi; Gwendoline Maharaux; Michèle Studer (Bio-Protocol)
Human brain development relies on a finely tuned balance between the proliferation and differentiation of neural progenitor cells, followed by the migration, differentiation, and connectivity of post-mitotic neurons with region-specific identities. These processes are orchestrated by gradients of morphogens, such as FGF8. Disruption of this developmental balance can lead to brain malformations, which underlie a range of complex neurodevelopmental disorders, including epilepsy, autism, and intellectual disabilities. Studying the early stages of human brain development, whether under normal or pathological conditions, remains challenging due to ethical and technical limitations inherent to working with human fetal tissue. Recently, human brain organoids have emerged as a powerful in vitro alternative, allowing researchers to model key aspects of early brain development while circumventing many of these constraints. Unlike traditional 2D cultures, where neural progenitors and neurons are grown on flat surfaces, 3D organoids form floating self-organizing aggregates that better replicate the cellular diversity and tissue architecture of the developing brain. However, 3D organoid protocols often suffer from significant variability between batches and individual organoids. Furthermore, few existing protocols directly manipulate key morphogen signaling pathways or provide detailed analyses of the resulting effects on regional brain patterning. To address these limitations, we developed a hybrid 2D/3D approach for the rapid and efficient induction of telencephalic organoids that recapitulate major steps of anterior brain development. Starting from human induced pluripotent stem cells (hiPSCs), our protocol begins with 2D neural induction using small-molecule inhibitors to achieve fast and homogenous production of neural progenitors (NPs). After dissociation, NPs are reaggregated in Matrigel droplets and cultured in spinning mini-bioreactors, where they self-organize into neural rosettes and neuroepithelial structures, surrounded by differentiating neurons. Activation of the FGF signaling pathway through the controlled addition of FGF8 to the culture medium will modulate regional identity within developing organoids, leading to the formation of distinct co-developing domains within a single organoid. Our protocol combines the speed and reproducibility of 2D induction with the structural and cellular complexity of 3D telencephalic organoids. The ability to manipulate signaling pathways provides an additional opportunity to further increase system complexity, enabling the simultaneous development of multiple distinct brain regions within a single organoid. This versatile system facilitates the study of key cellular and molecular mechanisms driving early human brain development across both telencephalic and non-telencephalic areas.